Implementation of a multicenter performance improvement program for early detection and treatment of severe sepsis in general medical–surgical wards. Issue 11 (2nd November 2016) - Schorr, Christa; Odden, Andrew; Evans, Laura; Escobar, Gabriel J.; Gandhi, Snehal; Townsend, Sean; Levy, Mitchell
Abstract : Sepsis is a leading cause of in‐hospital death, and evidence suggests a higher mortality in patients presenting with sepsis on the ward compared to those presenting to the emergency department. Ward patients who develop severe sepsis may have poor outcomes for a variety of reasons, including delayed diagnosis, lack of readily available staffing, and delayed treatment. We report on a multihospital quality improvement program for early detection and treatment of sepsis on general medical–surgical wards. We describe a multipronged approach to improve severe sepsis outcomes using the Institute for Healthcare Improvement's Plan‐Do‐Study‐Act model. Sixty sites engaged in a collaborative implementation process that aligned people, process, and technology. Based on our experience, we recommend a stepwise approach to implement such a program: (1) both administrative and clinical leadership commit to a common goal; (2) appoint clinical champions and give them authority to engage other clinicians to improve timeliness of interventions; (3) map workflows and processes to rely heavily on the nursing staff's ability to evaluate and report severe sepsis screening results; (4) if available, design and deploy technology with the assistance of clinical informaticians (eg, to enable electronic health records–based continuous screening); (5) to determine success, consider tracking screening compliance and process, and outcome measures such as length of stay and mortality. Journal of Hospital Medicine 2016;S11:32–S39. © 2016 Society of Hospital Medicine